Effects of Implicit Negotiation Beliefs and Moral Disengagement on Negotiator Attitudes and Deceptive Behavior - Tasa, Kevin (Journal of business ethics, 2017)
In three studies, we examined the relationship between implicit negotiation beliefs, moral disengagement, and a negotiator’s ethical attitudes and behavior. Study 1 found correlations between an entity theory that negotiation skills are fixed rather than malleable, moral disengagement, and appropriateness of marginally ethical negotiation tactics. Mediation analysis supported a model in which moral disengagement facilitated the relationship between entity theory and support for unethical tactics. Study 2 provided additional support for the mediation model in a sample of MBA students, whereby predispositions to morally disengage mediated the effect of dispositional entity beliefs on unethical behavior in a negotiation exercise. In study 3, we manipulated implicit beliefs prior to a negotiation simulation and found that entity beliefs predict deception through two sequential mediators, extreme opening bids and state moral disengagement.